2007
DOI: 10.1093/aob/mcm057
|View full text |Cite
|
Sign up to set email alerts
|

Hyperforin Accumulates in the Translucent Glands of Hypericum perforatum

Abstract: The accumulation of hyperforin detected in the translucent glands supports the proposed hypothesis that hyperforin is synthesized by the same biosynthetic machinery as monoterpenes in the chloroplasts of cells delimiting the gland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 15 publications
(21 reference statements)
5
40
0
Order By: Relevance
“…Although we could also detect minute amounts of adhyperforin in the dark glands, the deviation was higher. Our observation corroborates earlier studies which found that hyperforin is present in minute amounts in the dark glands, with a large proportion accumulating in the Btranslucent glands^, and almost no accumulation in the non-secretory tissues of the leaves [39]. Since these translucent glands are embedded sub-epidermally within the leaves and surrounded by thick layers of parenchyma cells [35], it was not possible for us to determine the distribution of hyperforin and adhyperforin in these glands using our noninvasive IMS techniques.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Although we could also detect minute amounts of adhyperforin in the dark glands, the deviation was higher. Our observation corroborates earlier studies which found that hyperforin is present in minute amounts in the dark glands, with a large proportion accumulating in the Btranslucent glands^, and almost no accumulation in the non-secretory tissues of the leaves [39]. Since these translucent glands are embedded sub-epidermally within the leaves and surrounded by thick layers of parenchyma cells [35], it was not possible for us to determine the distribution of hyperforin and adhyperforin in these glands using our noninvasive IMS techniques.…”
Section: Resultssupporting
confidence: 90%
“…2), with the objective of determining the tissue-specific site of accumulation of hypericin and structural analogues. Several intramarginal, mostly punctiform, black or blackishred dark glands could be observed on the leaves [35][36][37][38] in addition to numerous scattered, pale translucent glands [39]. Some of the dark glands had dark reddish coloring, particularly visible if observed under higher magnifications.…”
Section: Resultsmentioning
confidence: 99%
“…These two distinct types of glands are present in the plant parts like stem, flowers and leaves, although their distribution is different between species. EO and phloroglucinol derivatives, such as hyperforin are usually found in schizogenous translucent glands that appear as light points streaks when the leaves are held to the sun (Ciccarelli et al 2001;Soelberg et al 2007). Giuliani et al (2010) have shown that Hypericum androsaemum presents typical translucent, EO producing glands, which are distributed on the leaf along both margins (margin glands) and on the lamina (lamina glands).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these species produce a broad spectrum of valuable compounds, mainly naphthodianthrones (hypericin and pseudohypericin), phloroglucinols (hyperforin and adhyperforin), flavonoids (hyperoside, rutin or quercitrin), xanthones and essential oils that are associated with antiviral, antitumor, neuroprotective, antioxidant and antidepressant properties (Kirakosyan et al 2008). It has generally been accepted that these biologically active substances are synthesized, or accumulate in, different types of secretory structures including the dark glands, translucent glands, and secretory canals located in different organs of the plants (leaf, stem and flower tissues) (Soelberg et al 2007;Zobayed et al 2006;Kirakosyan et al 2008). A recent review by Bruni and Sacchetti (2009) shed light on the morphological and chemical variations among different Hypericum species and varieties.…”
Section: Introductionmentioning
confidence: 99%